1) х-2у=-16

5х+у=-3

2) х+2у=6

х-3у=-14

3) 3х-2у=-12

х+3у=-4

4)5х+2у=-9

х-3у=5

5) 3х+2у=-2

у+х=-1

6)х-у=5

2х+у=1

7)х+у=3

2х+3у=3

8)2х-у=8

х-у=5

9)х-4у=12

х+2у=6

10)х-4у=3

2х+у=15

1

Ответы и объяснения

  • irakim
  • почетный грамотей
2013-04-30T09:28:04+00:00

1) х-2у=-16                                        

   5х+у=-3

 х=-16+2у

5(-16+2у)+у=-3

-80+10у+у=-3

-80+11у=-3

11у=-3+80

11у=77

у=7

2) х+2у=6

   х-3у=-14

х=6-2у

6-2у-3у=-14

6-5у=-14

-5у=-14-6

-5у=-20

у=4

3) 3х-2у=-12

   х+3у=-4

х=-4-3у

3(-4-3у)-2у=-12

-12-9у-2у=-12

-12-11у=-12

-11у=-12+12

-11у=0

у=0

4)5х+2у=-9

   х-3у=5

х=5+3у

5(5+3у)+2у=-9

25+15у+2у=-9

25+17у=-9

17у=-9-25

17у=-34

у=-34:17

у=-2

5) 3х+2у=-2

  у+х=-1

х=-1-у

3(-1-у)+2у=-2

-3-3у+2у=-2

-3-1у=-2

-1у=-2+3

-1у=1

у=1:(-1)

у=-1

6)х-у=5

 2х+у=1

х=5+у

2(5+у)+у=1

10+2у+у=1

10+3у=1

3у=1-10

3у=-9

у=9:3

у=3

7)х+у=3

  2х+3у=3

х=3-у

2(3-у)+3у=3

6-2у+3у=3

6+1у=3

1у=3-6

1у=-3

у=-3

8)2х-у=8

  х-у=5

х=5+у

2(5+у)-у=8

10+2у-у=8

10+1у=8

1у=8-10

1у=-2

у=-2

9)х-4у=12

  х+2у=6

х=6-2у

6-2у-4у=12

6-6у=12

-6у=12-6

-6у=6

у=6:(-6)

у=-1

10)х-4у=3

   2х+у=15

х=3+4у

2(3+4у)+у=15

6+8у+у=15

6+9у=15

9у=15-6

9у=9

у=9:9

у=1